Shewanella: an important, emerging and lethal pathogen in a patient with recurrent presentations of cholangitis. Issue 12 (10th December 2020) - Hong, Jason; Steen, Christopher; Wong, Enoch; Keong, Ben
Abstract : We present a case of recurrent cholangitis caused by Shewanella algae, a lethal, emerging pathogen that clinicians should be made aware of. An 86-year-old man with a history of gastrectomy for peptic ulcer disease and a cerebrovascular accident with known choledocholithiasis presented with recurrent episodes of cholangitis that failed conservative antibiotic treatment regimens. Shewanella has been described to have increasing resistance to piperacillin and tazobactam. Both S. algae and multidrug-resistant Escherichia coli were co-isolated in this patient, which required broader spectrum antibiotics for successful treatment and management. A high index of suspicion is required if the history is suggestive of marine or aquatic exposure, which could expose the patient to this lethal pathogen. Re-thinking and re-taking the history are important cornerstones in refining the diagnosis when faced with recurrent presentations of the same problem.